Pharmacokinetic Studies of Bergapten in Dog Plasma by Using a LC-MS/MS Method Studies - Gao, Y.; Liu, Y. Z.; Zhang, X.-M.; Zhou, Y.; Zhang, X.; Dong, C.-Y. (Drug Research, 2013)
A sensitive LC-MS/MS method was developed for the determination of bergapten in dog plasma. The chromatographic separation was carried out on a Hypersil ODS column with a mobile phase consisting of methanol-water. The plasma sample was precipitated with methanol and prepare for injecting onto the LC-MS/MS system. The detection was performed on a triple quadrupole tandem mass spectrometer by MRM via electro spray ionization source. The standard curve for bergapten was linear over the concentration range of 0.5–500 ng/mL with a lower limit of quantification of 0.5 ng/mL. The inter-day and intra-day precision (R.S.D.%) for bergapten varied between 3.4 and 11.5. The corresponding inter-day and intra-day accuracy (Bias%) ranged between −3.8 and 6.9. For the pharmacokinetic analysis of serum, the mean (SD) values obtained for the bergapten were as follows: Cmax, 228.5 (14.3) ng/ml; Tmax, 4.2 (0.4) h; t1/2, 6.9 (2.3) h; AUC0–t h, 2507.2 (168.5) ng · h/mL and AUC0–∞, 3 219.2 (211.4) ng · h/mL, respectively.
Keywords: bergapten; LC-MS/MS; pharmacokinetics